2023
DOI: 10.1111/jsr.13858
|View full text |Cite
|
Sign up to set email alerts
|

Is camera recording crucial for the correct diagnosis of sleep bruxism in polysomnography?

Abstract: SummaryDue to potential issues, several sleep laboratories conduct sleep bruxism diagnosis without the use of a camera, instead relying mostly on electromyographic monitoring. The purpose of the study was to determine if a camera is necessary for the polysomnographic evaluation of sleep bruxism and how sleep bruxism parameters change when a camera is not utilised. The study material was actual polysomnographic recordings made in the years 2017–2020. A total of 199 single‐night video‐polysomnographic recordings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…It is very important to investigate the factors and effects of the combination of these two conditions. Epidemiological studies suggested that OSA patients are more likely to have SB (8), and this is supported by the findings of polysomnographic (PSG) studies showing that between 9 and 70% of OSA patients also have SB (10-14) and the body position-related OSA phenotype has higher SB and severe SB incidence (15). Genetic predisposition to OSA-SB relationship was also proposed previously (16).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…It is very important to investigate the factors and effects of the combination of these two conditions. Epidemiological studies suggested that OSA patients are more likely to have SB (8), and this is supported by the findings of polysomnographic (PSG) studies showing that between 9 and 70% of OSA patients also have SB (10-14) and the body position-related OSA phenotype has higher SB and severe SB incidence (15). Genetic predisposition to OSA-SB relationship was also proposed previously (16).…”
Section: Introductionmentioning
confidence: 74%
“…We cannot deny the possibility that OSA phenotypes can be heterogenous or biased with a small sample size. Although this study analyzed arousal threshold as one of physiological factors for defining the phenotypes, other physiological factors (loop gain etc.,) and the anatomical factors (e.g., craniofacial morphology) as well as the effect of body position (i.e., position related OSA) (15) were not considered for the analysis. In addition, the severity of most patients in this study were mild to moderate levels.…”
Section: Study Limitationsmentioning
confidence: 99%
“…A concordance between the EMG-EKG portable device and the PSG (gold standard) design was used with six participants without OSA and sixteen with OSA. The sample of OSA patients was segmented by the degree of severity in three groups: Mild OSA = 7 (AHI = 5-14.9/h), Moderate OSA = 3 (AHI = 15-29.9/h), Severe OSA = 6 (AHI ≥ 30/h) [78].…”
Section: Sample Selectionmentioning
confidence: 99%
“…In the SB and OSA group, the diagnosis was confirmed by PSG performed by a sleep expert, following blind masking concerning the clinical examination. The AHI (episodes of AH per hour) was used to categorize OSA groups by severity level, according to published criteria [34,78]. PSG Sleep Bruxism Analysis SB events were estimated through rhythmic (RMMA; Figure 2) and non-rhythmic masticatory muscle activity (MMA) recorded with EMG on the masseter muscles (surface electrodes).…”
Section: Psg Recordingsmentioning
confidence: 99%
“…There exists a theoretical “temporal” mechanism against OSA in concomitant SB and OSA where, during bruxism episodes, mandible protrusion maintains the patency of the upper airway tract [ 29 , 30 ]. COMISA syndrome consists of OSA and insomnia alone but it has not been estimated as to whether SB could have any connection in COMISA using a gold standard method to diagnose sleep disorders such as polysomnography with video-recording [ 31 ].…”
Section: Introductionmentioning
confidence: 99%